2017
DOI: 10.1016/j.aquatox.2017.02.027
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fipronil and the photodegradation product fipronil desulfinyl on growth and gene expression in juvenile blue crabs, Callinectes sapidus, at different salinities

Abstract: Endocrine disrupting compounds (EDCs) are now widely established to be present in the environment at concentrations capable of affecting wild organisms. Although many studies have been conducted in fish, less is known about effects in invertebrates such as decapod crustaceans. Decapods are exposed to low concentrations of EDCs that may cause infertility, decreased growth, and developmental abnormalities. The objective herein was to evaluate effects of fipronil and its photodegradation product fipronil desulfin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 73 publications
0
30
0
Order By: Relevance
“…On the contrary, Goff et al . 33 found that juvenile blue crabs Callinectes sapidus exposed to different nominal concentrations of fipronil and fipronil desulfinyl resulted in significant increases in growth in all treatments compared to controls in a short-term (96-h) experiment.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…On the contrary, Goff et al . 33 found that juvenile blue crabs Callinectes sapidus exposed to different nominal concentrations of fipronil and fipronil desulfinyl resulted in significant increases in growth in all treatments compared to controls in a short-term (96-h) experiment.…”
Section: Discussionmentioning
confidence: 89%
“…Fipronil desulfinyl (a photodegradation product of fipronil) was detected in the eggs of the Atlantic blue crab Callinectes sapidus off the coast of South Carolina (the Eastern coast of the United States), and it may be one of the causes of C . sapidus decline to the lowest historical levels over the past decade 33 . In Texas, fipronil has been reported in several recent studies conducted by the U.S. Geological Survey (USGS) and U.S. EPA in different cities including Houston-Galveston 48 , Austin 49 , San Antonio 50 , and College Station 51 , in concentrations ranging between 0.021 μg/L and 0.075 μg/L.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We further tested a suite of potential dose-response functions among concentrations, because fitting curves better allows for insights into dose-response patterns and also provides increased statistical power compared to testing for pairwise differences between treatments with an ANOVA / Tukey post-hoc approach (Cottingham et al, 2005; Brander et al, 2016; Goff et al, 2017). Therefore, per methods developed in Brander et al, 2016 and applied in Frank et al (2018), five different dose-response curves (linear regression, quadratic, sigmoidal, 5-parameter unimodal, and 6-parameter uni-modal) were tested for the best-fit of observed responses at all three concentrations and the solvent control (MeOH).…”
Section: Methodsmentioning
confidence: 99%
“…various kinds of attention in utilization pesticide because of the contaminant effect against living things [1,2]. One of pesticide used in agriculture is fipronil which is categorized as persistent organic pollutants (POPs) waste [3]. POPs is phenol pollutant waste in low-concentration where accumulated in the aquatic environment and contacted with living things.…”
Section: Introductionmentioning
confidence: 99%